Surface nanorelief modification of constructional materials at low energy ion bombardment - Kalinichenko, A.I.; Perepelkin, S.S.; Strelnitskij, V.E. (Вопросы атомной науки и техники, 2016)
Process of thermal smoothing at bombardment of metal surfaces by low energy heavy ions is investigated. It is shown, that smoothing can occur in nonlocal thermoelastic peak of ion under action of forces of surface tension at spreading the melted material on the surface. The model of thermal smoothing alternative to model of ion polishing due to ion sputtering of target atoms is developed. Criteria of applicability of model for any combination “ion–target”, and analytical expressions for basic parameters of process of smoothing (size of smoothing area created by single ion, time of smoothing) are received. Теоретично досліджувався процес теплового згладжування при бомбардуванні металевих поверхонь важкими іонами низьких енергій. Показано, що вирівнювання поверхні може відбуватися під дією сил поверхневого натягу при розтіканні уздовж поверхні розплавленого матеріалу, що утворюється в нелокальному тепловому піку іона. Розроблено модель теплового згладжування, яка альтернативна моделі іонного полірування за рахунок розпилення іонів мішені. Отримано критерії, що визначають застосовність моделі для довільної комбінації «іон-мішень», і аналітичні вирази для основних параметрів процесу згладжування (розмір області згладжування, яка створювана одиночним іоном, час згладжування). Теоретически исследовался процесс теплового сглаживания при бомбардировке поверхности металлов тяжелыми ионами низкой энергии. Показано, что выравнивание поверхности может происходить под действием сил поверхностного натяжения при растекании вдоль поверхности расплавленного материала, образующегося в нелокальном тепловом пике. Разработана модель теплового сглаживания, альтернативная модели ионной полировки, за счет ионного распыления. Получены критерии, определяющие применимость модели для произвольной комбинации «ион-мишень», а также аналитические выражения для основных параметров процесса сглаживания (размер области сглаживания, создаваемой одиночным ионом, время сглаживания).